Development of E-Book and Quizizz-Based Interactive Quizzes to Enhance Learning Evaluation Engagement of Fifth-Grade Elementary School Students - Latri Aras; Arini Arianty (Sains Global Institut, Indonesia, 2026)
This study aims to develop learning media in the form of an e-book and interactive quizzes based on Quizizz to enhance students' engagement in learning evaluation at the elementary school level. The study employed a Research and Development (R&D) method using the Borg and Gall development model, which consists of ten stages of product development. However, this research was limited to the product development stage and theoretical evaluation through a literature review approach without conducting direct field testing. Data were collected through a literature study by reviewing various scientific sources, including books, national journals, and relevant previous research findings. The results of the review indicate that the use of digital learning media such as e-books and Quizizz has the potential to increase students' motivation, engagement, and active participation in learning evaluation activities. Therefore, the developed media are considered theoretically feasible as an innovative learning evaluation tool that aligns with the characteristics and needs of elementary school students.